Spinacia oleracea L. CGN09415 ... - GLIS Of The ITPGRFA (Centre for Genetic Resources, the Netherlands, 2017)
Plant Genetic Resource. Taxonomy: Spinacia oleracea L. Common name(s): spinach Other names: Groenland Conserved by: Centre for Genetic Resources, the Netherlands (CGN), Netherlands (Kingdom of the) Local sample unique identifier: CGN09415 Method of creation: Acquisition Date: 1988-10-13 Other identifiers: purl,http://purl.org/cgngenis/accenumb/CGN09415 Historical: No Biological status: Advanced or improved cultivar MLS status: Not included ...